The Production Of Astaxanthin In Freshwater Algae, Haematococcus Pluvialis with Lead Nanopparticle Exposure - Rasheed, Nasma (2018)
Haematococcus pluvialis is a freshwater micro alage the produces up to 4-5 % dry witght of astaxanthin making it the most effective orgaisms for astaxanthin production. Astaxanthin is a ketocarotenoid with high antioxidant properties. It is used in feed, nutraceutical, food, pharmaceutical and various other industries owing to its high antioxidant level. Astaxanthin is accumulated under stress in H. pluviallis and the effect of lead (Pb) nanoparticles exposure on the production of astaxanthin in H. pluvialis. In this experiment, H. pluvialis was cultured in Bold Basal Medium (BBM) and exposed to three concentrations (10 mg/L, 100 mg/L and 200 mg/L) of lead nanoparticles in the form of Pbo nanopaerticles. Cell quantification was done in every 2-3 days using cell counting chamber and light microscope. Astaxanthin was then extracted and qualified at 470 nm using a spectrophotometer in every 4-5 days. Negative control without PbO nanoparticles was also cultured in order to compared astaxanthin production in stressed and unstressed cells. The data were staistically analyzed using simple tools in Microsoft Excel 2016. Growth curve of H. pluvialis cells showed that the cells experienced three phases of cell growth and showed the highest cell density of 16.92 x 10 cells/mL. The results showed that the cells exposed to PbO nanoparticles did not yield a higher percentage of astaxanthin compared with unstressed cells due to the decreased cell number. The maximum amount of astaxanthin (0.235 mg/L) was accumulated in negative control cells. Therefore, H pluvialis underwent lag phase, log phase and stationary phase. Exposure of lead nanoparticles did not yield a high amount of astaxanthin compared with negative control due to the less incunation period PbO causing a negative effect on H. pluvialis cell density.